2004
DOI: 10.1158/1078-0432.ccr-0320-03
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Transforming Growth Factor β Receptor II in Estrogen Receptor-Negative Breast Cancer Patients

Abstract: Purpose: The role of transforming growth factor ␤ (TGF-␤) in breast cancer is ambiguous; it can display both tumor suppressing and enhancing effects. Activation of the TGF-␤ signal transduction system is subject to hormonal regulation. This study was conducted to further analyze the role of TGF-␤ receptors in breast cancer and to evaluate their significance as prognostic markers. Experimental Design: Expression of TGF-␤ receptor I (T␤RI) and TGF␤ receptor II (T␤RII) was retrospectively analyzed by immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 32 publications
(20 reference statements)
7
73
2
4
Order By: Relevance
“…By KaplanMeier analysis, we identified a correlation between the expression of TGF-b receptor II and a highly reduced overall survival in ER-negative breast cancer patients [14]. These findings indicate a coupling of both groups in a functional network and strongly presume a crosstalk between ERa and components of the TGF-b pathway in breast cancer cells.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…By KaplanMeier analysis, we identified a correlation between the expression of TGF-b receptor II and a highly reduced overall survival in ER-negative breast cancer patients [14]. These findings indicate a coupling of both groups in a functional network and strongly presume a crosstalk between ERa and components of the TGF-b pathway in breast cancer cells.…”
Section: Introductionmentioning
confidence: 69%
“…This mechanism also explains the role of TGF-b in ERa-positive and ERa-negative patients according to the overall survival, which we studied in 2004. The expression of TGF-b receptor type II in ERanegative patients is correlated with highly reduced overall survival, whereas simultaneous loss of both ERa and TGF-b receptor type II is comparable with down-regulation of TGF-b signaling and was associated with longer overall survival [14]. Moreover, the inhibitory function of ERa is independent from the ligand-dependent receptor function and a loss of ERa would result in a poor prognosis, which actually was shown in several studies [1,2,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, we demonstrate that TGFBR2 is expressed at higher levels in more aggressive basal‐like breast cancer cell lines as well as in triple‐negative breast cancer tissue than in luminal breast cancer cell lines and luminal‐like tumor tissue. This subtype‐specific expression of TGFBR2 might explain why TGFBR2 expression correlates with reduced overall survival of patients with ER‐negative but not with ER‐positive breast cancer (Buck et al ., 2004). Nevertheless, the exact mechanisms of TGFβ1/TGFBR2‐driven breast cancer progression and metastasis have not been fully elucidated until now.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that TGFβ signaling and TGFβ receptor type‐2 (TGFBR2) seem to have a tumor promoting role in human estrogen receptor (ER)‐negative breast cancer (Keklikoglou et al ., 2012). In addition, clinical studies in ER‐negative breast tumors indicated a correlation of elevated TGFBR2 levels with shorter overall breast cancer patient survival (Buck et al ., 2004). However, the molecular mechanisms of TGFβ signaling and elevated TGFBR2 expression are likely diverse and have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%